(untitled) (Medicine Today, 2017)
When foetal ascites is found alone (i.e., without other signs of hydrops), it may represent a separate problem requiring a different management strategy, leading to a different outcome. A 24-year-old primigravida was referred to our institution at 27 weeks of gestation with a diagnosis of isolated foetal ascites. No other pathology was detected on ultrasonography or a laboratory examination. The patient delivered a male infant weighing 3020 g at 38 weeks of gestation with Apgar scores of 7 and 9 at 1 and 5 minutes, respectively. The newborn was operated on by a paediatric surgery team with an indication of intrauterine extra-hepatic bile duct perforation in the first post-partum week, and was subsequently discharged from the hospital without any complications. Isolated foetal ascites is a rare and separate situation from foetal hydrops. The perinatal outcome for isolated ascites is much better than that for hydrops foetalis. Medicine Today 2017 Vol.29(1): 47-49